A pilot, family-based randomised controlled trial to reduce screen time and unhealthy snacking in children and their parents: Kids FIRST - Natalie Pearson; Stuart JH Biddle (Frontiers Media S.A., 2015)
Background The tendency for screen viewing and unhealthy eating behaviours to aggregate in young people has important implications for health promotion. There is much evidence highlighting the importance of parents and the family environment on young people's screen time and dietary behaviours. However, few interventions target the family and home environment, and little is known about the most feasible and effective behaviour change strategies for reducing screen time and unhealthy snacking in a family setting. Interventions that target both screen time and snack food intake have the potential to offer greater health benefits, more adequately address participants' behavioural profiles, and maximize health promotion opportunities. There is a need for family-based studies that examine both single (screen time and unhealthy snacking separately) and multiple (screen time and unhealthy snacking simultaneously) behaviour interventions to examine whether reductions in one behaviour result in reductions in the other. Aim To provide an overview of the development of 'Kids FIRST'; a novel, pilot family-based intervention comprising strategies and resources aimed at reducing screen-time and unhealthy snacking in children and their parents. Methodology Kids FIRST is a four arm cluster randomised controlled pilot trial, with schools as the unit of randomisation. Schools are allocated to one of four intervention groups: (1) Reducing unhealthy snacking at screens (both eating and screen-time); (2) Reducing screen-time only; (3) Reducing unhealthy snacking only; (4) Control (usual practice). The intervention is being piloted in children aged 5-6 years and 10-11 years and their parents. Children and parents receive the intervention over a 13-week period. It is delivered through group based face-to-face sessions with parents, class lessons in school, and the Kids FIRST website. The intervention components and modes of delivery were informed by preliminary cross-sectional research with children and parents. Potential mediators of behaviour change were determined based on our preliminary research, and were linked to behaviour change theories (Behavioural Choice Theory and Social Cognitive Theory) for the development of behaviour change techniques and intervention strategies. The Kids FIRST intervention is focused on providing parents and children with support in the form of Informational and Cognitive, Behavioural, Environmental, and Social Support intervention components as a means of empowering families to make behavioural changes that are specific to them. Each intervention group will receive the exact same schedule of intervention but the content will be specific to each group. Parents and children will be invited to take part in the evaluation assessments at baseline (week 0), post-intervention (week 14), and 6-months after baseline assessments. Primary outcomes are child and parent screen-time and energy-dense snack food consumption. Discussion To our knowledge, Kids FIRST is the first pilot RCT to examine the effectiveness of behaviour change strategies for reducing children's screen-time and unhealthy snacking. The integration of consistent, evidence-based and theory informed strategies and messages to children and their parents in the family and school settings are critical components of this pilot study. The results of this study will provide evidence on the feasibility and effectiveness of single versus multiple behaviour intervention strategies. If shown to be feasible and effective, the Kids FIRST study may have a significant impact on the home environment and parenting practices relating to screen time and unhealthy snacking.